Forest and landscape restoration at Pontal do Paranapanema: ecological attributes of forest restoration in a coffee agroforestry system - Badari, Carolina Giudice (2019)
A direct consequence of disorganized human population growth and the indiscriminate use of natural resources are the reduction of area and the fragmentation of native ecosystems, as they transform into agricultural areas. In this scenario, agroforestry systems (AFS) may be an alternative to reconcile restoration, conservation and local agricultural production. However, there is a diversity of AFS, and its use as a forest restoration strategy is still uncertain, mainly because we lack evaluations based on ecological indicators from those systems. Thus, we compared ecological indicators measured in a coffee agroforestry system in the Pontal do Paranapanema with those inform conventional restoration plantings of the same age and with regional reference ecosystems. We measured natural regeneration density and richness; canopy cover by native species and aboveground biomass and compared among sites using an ANOVA, followed by Tukey\'s test for mean comparison. Aiming to understand the factors influencing the ecological indicators of forest restoration in coffee AFS, we performed generalized linear models (GLM) using density of coffee and native trees, biomass, percentage of animal-dispersed trees, distance to the nearest forest remnant and richness of tree species as predictor variables and percentage of canopy cover and density and richness of natural regeneration as response variables. The reference forests had the highest values for forest structure indicators, followed by AFS and finally by the conventional restoration plantings. However, we found a greater diversity of tree species planted in the AFS and a natural regeneration similar to that found in the reference ecosystems. Despite coffee density in the AFS negatively influencing natural regeneration, the coffee AFS had greater ecological performance than the conventional restoration, being a viable alternative for forest restoration. We conclude that AFS with coffee and native tree species play an important ecological role in the FLR in Pontal do Paranapanema, reconciling productivity with forest restoration.